Palmas, the last capital city planned in twentieth-century Brazil - Rego,Renato Leão (2020)
Abstract Palmas is the capital of a new state created in order to foster regional development in central Brazil. This new town was planned from scratch in 1989, during the country’s re-democratization process, between the postmodernist criticism of functionalist planning and rising environmental concerns. However, its layout depicts a mixed relationship with Brasília-style urbanism. Covering a timeframe of thirty years (1989-2019), this paper presents an outline of the history and planning of Palmas, followed by an assessment of its plan and an exploration of its contemporary major urban challenges. It contrasts the planners’ original ideas with the built city, and unveils late modernist features that have been rejected and transformed. Essentially, Palmas is a modernist new capital city planned in postmodernist times.